2015
DOI: 10.1515/frp-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 nanoparticles on drought resistance in hawthorn seedlings

Abstract: Drought is a significant factor limiting crop production in arid regions while hawthorns (Crataegus sp.) are an important component of such region’s forests. Therefore, treatments that increase hawthorn drought resistance may also increase transplanting success. Thus, the physiological and biochemical responses of hawthorn seedlings to a factorial combination of different concentrations of silica nanoparticles (SNPs at 0, 10, 50 and 100 mg L−1) and three soil moisture treatments (without stress, moderate stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 48 publications
8
60
0
Order By: Relevance
“…However the combined treatments were more effective in enhancing the synthesis and accumulation of total chlorophylls, total carbohydrates and K% in leaves than individual one. The results of increasing total carbohydrates, N% or K% as a result of gypsum treatments are in conformity with that demonstrated by prior studies (Mora et al 1999;Arafa et al 2002;Lee and Mudge, 2013), while increasing in total chlorophylls, N% or K% as a result of nano silicon treatments are consistent with those reported by other studies (Bao-shan et al 2004;Li et al 2012;Xie et al 2012;Ashkavand et al 2015;Janmohammadi et al 2016, Sharifi-Rad et al 2016. The results of increasing total carbohydrates as a result of nano silicon treatments are disagreement with findings of Ashkavand et al (2015) who reported decreasing in carbohydrate contents due to application of SiO 2 nanoparticles.…”
Section: Chemical Constituentssupporting
confidence: 91%
See 1 more Smart Citation
“…However the combined treatments were more effective in enhancing the synthesis and accumulation of total chlorophylls, total carbohydrates and K% in leaves than individual one. The results of increasing total carbohydrates, N% or K% as a result of gypsum treatments are in conformity with that demonstrated by prior studies (Mora et al 1999;Arafa et al 2002;Lee and Mudge, 2013), while increasing in total chlorophylls, N% or K% as a result of nano silicon treatments are consistent with those reported by other studies (Bao-shan et al 2004;Li et al 2012;Xie et al 2012;Ashkavand et al 2015;Janmohammadi et al 2016, Sharifi-Rad et al 2016. The results of increasing total carbohydrates as a result of nano silicon treatments are disagreement with findings of Ashkavand et al (2015) who reported decreasing in carbohydrate contents due to application of SiO 2 nanoparticles.…”
Section: Chemical Constituentssupporting
confidence: 91%
“…Also it was clear that there is no significant difference between application of nano silicon at 1 or 2 mM concentration in most cases. Similar increases in growth and flowers parameters as a result of gypsum treatments have been reported by prior studies (Arafa et al 2002;Kakaraparthi et al 2013;Kumar et al 2014) , also such increases due to nano silicon treatments confirmed the reports of other researches (Bao-shan et al 2004;Ashkavand et al 2015;Janmohammadi et al 2016;Sharifi-Rad et al 2016 andKhalaki et al 2016). Additionally, previous studies (Kamenidou andCavins, 2008 &Sivanesan et al 2013) reported that application of Si in bulk materials (potassium silicate or sodium silicate) increased plants growth and flowering parameters.…”
Section: Vegetative Growth and Flowering Parameterssupporting
confidence: 88%
“…So, SNPs aided plants to maintain root length and decreased the impact on XWP but not on RWR. In this respect, Zhang et al (2013) found that silicon application did not enhance leaf RWC of Chestnut plants subjected to water deficit as well as it was found by Ashkavand et al (2015) on hawthorn seedlings. Curiously, it seems that SNPs application did not aid to improve leaf RWC in woody plants (eg.…”
Section: Discussionmentioning
confidence: 75%
“…Curiously, it seems that SNPs application did not aid to improve leaf RWC in woody plants (eg. Zhang et al, 2013;Ashkavand et al, 2015) but it does it in herbaceous crop species such as sorghum (Kafi et al, 2011), cotton, canola, and wheat (Mehrabanjoubani et al, 2015). Gadallah (2000) proposed that RWC improvement could be due to (i) an enhanced water uptake resulting from a more developed root system and (ii) a reduction of water loss by transpiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation